High prevalence of alpha-thalassemia among individuals with microcytosis and hypochromia without anemia - Borges,E. (2001)
In order to determine the contribution of alpha-thalassemia to microcytosis and hypochromia, 339 adult outpatients seen at Unicamp University Hospital (with the exception of the Clinical Hematology outpatient clinics), who showed normal hemoglobin (Hb) levels and reduced mean corpuscular volume and mean corpuscular hemoglobin, were analyzed. Ninety-eight were Blacks (28.9%) and 241 were Caucasians (71.1%). In all cases, Hb A2 and F levels were either normal or low. The most common deletional and nondeletional forms of alpha-thalassemia [-alpha3.7, -alpha4.2, --MED, -(alpha)20.5, alphaHphIalpha, alphaNcoIalpha, aaNcoI and alphaTSAUDI] were investigated by PCR and restriction enzyme analyses. A total of 169 individuals (49.9%) presented alpha-thalassemia: 145 (42.8%) were heterozygous for the -alpha3.7 deletion (-alpha3.7/aa) and 18 (5.3%) homozygous (-alpha3.7/-alpha3.7), 5 (1.5%) were heterozygous for the nondeletional form alphaHphIalpha (alphaHphIalpha/aa), and 1 (0.3%) was a --MED carrier (--MED/aa). Among the Blacks, 56 (57.1%) showed the -alpha3.7/aa genotype, whereas 12 (12.2%) were -alpha3.7/-alpha3.7 and 1 (1.0%) was an alphaHphIalpha carrier; among the Caucasians, 89 (36.9%) were -alpha3.7/aa, 6 (2.5%) had the -alpha3.7/-alpha3.7 genotype, 4 (1.7%) presented the nondeletional form (alphaHphIalpha/aa), and 1 (0.4%) was a --MED carrier. These results demonstrate that alpha-thalassemia, mainly through the -alpha3.7 deletion, is an important cause of microcytosis and hypochromia in individuals without anemia. These data are of clinical relevance since these hematological alterations are often interpreted as indicators of iron deficiency.